The influence of hypoxic training on preparedness of sportsmen who are specialized in types of endurance - Lyudmyla Shesterova; Tu Yanhao; Gennadiy Budkevich (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to study the problem of the influence of training in conditions of middle mountains and highlands on a functional state and preparedness of sportsmen who are specialized in types of endurance on the basis of the analysis of references. Materials and methods: analysis and synthesis of references. Results: the processing of information allowed to define the extent of influence of training in mountain conditions and in the conditions of an artificial hypoxia on a functional state and sports result of the highly skilled sportsmen who are specialized in types of endurance. Conclusions: it is defined that the correct organization of the training process in middle mountains and highlands allows not only to expand the functionality of organism of runners, but also to improve the technique of run.